Education in the Context of SDG 4.7: Integration of Education for Sustainable Development (ESD) and Global Citizenship Education (GCED) in School Curriculum - Raveendran, Ashita (THE PRIMARY TEACHER, 2019)
This paper focuses on integration of Education for Sustainable Development (ESD) and Global Citizenship Education (GCED) in school curriculum in the context of the target 4.7 of the Sustainable Development Goal (SDG) that is to be achieved by the member nations by 2030. Curricular practices need to promote sustainable lifestyle so as to enable the learner to decrease the carbon foot print and live in harmony with the environment. The curricular practices that have been implemented in various parts of the country and how they have helped in inculcation of values and competencies required for a global citizen has been elucidated. The paper also puts forth the transformative pedagogies that can help learners in acquiring the skills and competencies needed for achieving the target.